Identification Of Antigens Recognized By The Monoclonal Antibody, IBMR3 On Lymphocytes And Established Cell Lines - Aris, Farizan (2016)
Monoclonal antibodies have demonstrated significant utilities in both research and clinical applications. IBMR3 monoclonal antibody (IBMR3 MAb) has been shown to recognize a molecule that may be associated with the human interleukin-4 receptor (IL-4R) complex. IL-4 has been shown to be extensively associated with cancer. The aim of this study is to identify the IBMR3 antigen (IBMR3 Ag) expressed in normal peripheral blood mononuclear cells (PBMC) and in a panel of established cell lines. Immunostaining revealed that IBMR3 MAb can recognize antigen in a variety of cell types, including epithelial, fibroblast, haemopoietic, cancer, and normal cells. Interestingly, IBMR3 Ag was found to be expressed in the cytoplasm but was absent on the cell surface except for normal lymphocytes.